Sculptural Portraits à l’antique: to the Problem of Iconographic Identification - Karpova, Elena V. (Actual Problems of Theory and History of Art, 2015)
Classicism introduced a characteristic antiquitization of an individual depicted on sculptural portraits. Uniforms and medals, which could be used to accurately establish the time when a work was created and the nationality and social position of an individual, were left in the past. Museum practice shows that in course of studying such a portrait à l’antique, the determination of its previously unknown provenance plays a special role. Thus, the Portrait of an Unknown Man by Josef Kirchmayer (1818, State Russian Museum) from the Leuchtenberg collection shows Prince Eugene de Beauharnais (1781–1824), the founder of the Leuchtenberg family. An additional complication to the study of portraits à l’antique is scarce information about its creators. The attribution of the Portrait of a Soldier (1825, State Hermitage), a work by minor Italian sculptor Giulio Kravari is an example of the case where an iconographic research obtains special importance: the study revealed that it is a marble bust of Count Pavel Shuvalov (1776–1823). An attempt to solve the dilemma of “looks like/does not look like” can often lead to highly subjective conclusions. Sculpture, however, with its inherent three-dimensionality and the possibility to see the depicted face foreshortened in different ways, allows us to get a more complete understanding of the appearance of the portrayed person. This helps us to reject the existing incorrect attributions. An example of such is the renaming of the so-called Portrait of Nicholas I, a work by Tomasz Oskar Sosnowski from the National Museum, Warsaw. An archival survey was a way to gather information for renaming that bust as that of Count Fiodor Berg (1794–1874).